Assessment, distribution and speciation of heavy metals (Zn, Cu, Pb, Ni, Cd and Fe) in surface sediment and different parts of Dreissena polymorpha along the South Coast of the Caspian Sea and Anzali Wetland, Iran - Sohrabi, Tooraj (2011)
This study was concentrated on speciation and fractionation of heavy metals (Pb,Ni, Cd, Zn, Cu and Fe) on surface sediments of the south Caspian Sea as a biggest Lake in the world and Anzali wetland as an international important wetland registered in the Ramsar convention during 2008-2009. Concentrations of heavy metals in bivalve Dreissena polymorpha also were determined to assess the status of heavy metals pollution in the south of the Caspian Sea. There was no study before about the peciation, fractionation of heavy metals in the surface sediment of south Caspian Sea and Anzali wetland. Because of living more than 10 million people in this area, assessment of anthropogenic input on surface sediment and influence of that on bivalve as a food of sturgeons can be important. The Aqua Regia method and sequential extraction technique ”easily, freely, leachable and exchange-able (EFLE)‟, “acid-reducible”, “oxidisable organic” and “resistant” were used for analyses of total concentration and geochemical fraction of heavy metals from 14 sites of south Caspian Sea and 6 sites of Anzali wetland. The air-acetylen flame atomic absorption spectrophotometer (AAS) Perkin-Elmer Model 4100 was used for determination of heavy metals. The metal levels were evaluated according to the Enrichment Factor (EF), Pollution Index (PLI) and Geoaccumulation Index (I geo) analyses.Total Metal concentrations (μg/g; except Fe%) showed variations with Pb, 13.06-33.48; Ni, 18.01-69.63; Cd, 0.62-1.5; Zn, 30.11-87.88; Cu, 5.86- 38.89; Fe, 1.8-4. Concentration of heavy metals in surface sediment were found to be higher in some sites close to ports, urban areas and ship transport areas in the west and east of the Caspian Sea with anthropogenic activities. Measured EF and PLI for all metals in the west of Caspian Sea were higher than other sites. Cadmium showed higher EF and PLI when compared to other metals. The average enrichment factor of cadmium (8.71±2.86) was determined to be higher than 5 in surface sediment of the south Caspian, which indicated that Cd contamination, had moderately severe enrichment. I geo value for Cd in most stations which was classified as moderately contaminated and moderately to strongly contaminated, as well as the average of I geo of Cd (1.77±0.35) suggested that surface sediments of Caspian coast were moderately polluted by this metal. All of the metal concentrations in sediments for 14 sampling Stations (Pb, Ni, Zn, Cu and Fe)except Cd were dominated by the resistant fractions. The non-resistant fractions were lower than the resistant fractions for the whole duration of the study, which indicated that there were no significant anthropogenic inputs of Pb, Ni, Zn, Cu and Fe to the surface sediments of south Caspian Sea. The high percentages of nonresistant geochemical fractions of Cadmium indicated that sources of Cd in surface sediments of the south Caspian Sea were mainly contributed from anthropogenic sources. Results revealed that heavy metal pollution is mainly localized in the west of the Caspian Sea in port areas devoted to shipping, agriculture and Azerbaijan activities and in the east, which is under the influence of industrial activities.The mean concentrations of each metal varied for the soft tissue, shell and byssus of D. polymorpha. Concentrations of Ni, Cd, Cu and Fe were found to be highest in byssus, whilst highest oncentrations of Pb and Zn were recorded in shell and soft tissue, respectively. This suggested that, the byssus of D. polymorpha can be used as biomonitoring agent for Ni, Cu, Fe and especially Cd because of a high positive correlation of Cd in the byssus with fractions of sediments.For Anzali wetland, generally, Shanbe Bazar showed the highest level of Pb (69.10 μg/g dw); Ni (71.79 μg/g dw); Cd (1.81 μg/g dw); Zn (830.95 μg/g dw); Cu (89.54 μg/g dw). Shanbe bazaar is located in the urbanized area of Anzali city and may receive heavy pollution through municipal effluents. Also highest concentration of EFLE and oxidisable organic fractions of heavy metals (Pb, Ni, Cd, Zn, Cu and Fe) in comparison with other sampling sites was recorded in Shanbe Bazar. Most of the metals were strongly and positively correlated. The strong positive relationships between the Pb, Cd, Zn and Cu indicated that the sources of both natural and anthropogenic inputs were similar. Higher percentages of heavy metals in the nonresistant fraction reflect a grater tendency to become bioavailable.Studying the effects of metal concentration on the gill of the zebra mussel collected from special sites of the Caspian Sea by transmission electron microscopy showed that ultramorphology technique is good tool to study cell alterations used as biomarkers, being efficient in the analysis of environment. It was clear that the zebra mussel in polluted sites suffered changes related to the respiratory system